2022
DOI: 10.21203/rs.3.rs-1950116/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterologous biosynthesis of isobavachalcone in tobacco based on in planta screening of prenyltransferases

Abstract: Isobavachalcone (IBC) is a prenylated chalcone mainly distributed in some Fabaceae and Moraceae species. IBC exhibits a wide range of pharmacological properties, including anti-bacterial, anti-viral, anti-inflammatory, and anti-cancer activities. In this study, we attempted to construct the heterologous biosynthesis pathway of IBC in tobacco ( Nicotiana tabacum ). Four previously reported prenyltransferases, including GuILDT from Glycyrrhiza uralensis , HlPT1 from Humulus lupulus , and SfILDT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…[58,59] In Figure 5A, the reversible switching between Fe 2+ and Fe 3+ oxidation states has been illustrated which results in ROS production and scavenging through the oxidation-reduction cycles. The antioxidant activities of IONzymes benefits the therapeutic effects during wound healing process [34,60,61] (Figure 5B,C). Prussian blue ) is an iron-based coordination compound and PB-based nanoparticles show great enzyme mimetic properties and anti-inflammatory activities.…”
Section:  Iron-based Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[58,59] In Figure 5A, the reversible switching between Fe 2+ and Fe 3+ oxidation states has been illustrated which results in ROS production and scavenging through the oxidation-reduction cycles. The antioxidant activities of IONzymes benefits the therapeutic effects during wound healing process [34,60,61] (Figure 5B,C). Prussian blue ) is an iron-based coordination compound and PB-based nanoparticles show great enzyme mimetic properties and anti-inflammatory activities.…”
Section:  Iron-based Nanomaterialsmentioning
confidence: 99%
“…This electrospun hybrid nanofibrous wound dressing possesses high catalase-like enzymatic activity to quickly convert H 2 O 2 into O 2, as well as excellent wettability, water permeability, and cell proliferation in wounds. Guo et al [60] synthesized IONPs to promote peroxide-like catalytic activity for bacteria-infected wound therapy. They found that IONPs induced conversion of H 2 O 2 to hydroxyl radicals to prevent bacterial infection and biofilm formation, leading to efficiently enhanced wound healing in mouse models.…”
Section:  Iron-based Nanomaterialsmentioning
confidence: 99%